Systematic review of ototoxic pre-surgical antiseptic preparations – what is the evidence? - Shubhi Singh; Brian Blakley (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objective There is uncertainty regarding the safety of surgical antiseptic preparations in the ear. A systematic review of the literature was conducted to assess the evidence regarding ototoxicity of surgical antiseptic preparations. Methods A literature search was conducted using the PRISMA methods. Key words included “ototoxicity” “hearing loss”, “antiseptic”, “surgical preparation”, “tympanoplasty”, “vestibular dysfunction”, “chlorhexidine”, “iodine”, “povidone”, “ethanol”, and “hydrogen peroxide” using Medline, Embase, Cochrane Library, Scopus and Web of Science. We included peer-reviewed papers that 1) objectively measured ototoxicity in humans or animals through hearing, vestibular function or histologic examination, 2) studied topically applied surgical antiseptic preparations, 3) were either in English or had an English abstract. We excluded papers that were 1) in vitro studies, 2) ear trauma studies, 3) studies of ototoxic ear drops intended for therapy, or 4) case reports. Studies included in the final review were screened using the PRISMA method. Current systematic review registration number pending: 83,675. Results Fifty-six papers were identified as using PRISMA criteria. After applying our exclusion criteria, 13 papers met overall study criteria. Of these, six papers reported ototoxicity of iodine based solutions, five papers reported ototoxicity of chlorhexidine and ethanol and two papers assessed hydrogen peroxide. All papers reviewed were animal studies. Iodine based solutions show least harm overall, while chlorhexidine and high concentrations of alcohol based solutions showed most harm. The evidence on hydrogen based solutions was inconclusive. Conclusions The overall evidence for anyone antiseptic solution is weak. There is some evidence that iodine, chlorhexidine, hydrogen peroxide and alcohol based antiseptics have ototoxicity. Conclusive evidence for human ototoxicity from any solution is not strong.